Transactions on Engineering Technologies - Ao, Sio-Iong.; Yang, Gi-Chul.; Gelman, Len.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This volume presents selected peer-reviewed, revised and extended research articles written by prominent researchers who participated in the World Congress on Engineering 2015, held in London, UK, 1-3 July, 2015. This large international conference covered advances in engineering technologies and the physical sciences, with contributions on subjects including mechanical engineering, bioengineering, internet engineering, image engineering, wireless networks, knowledge engineering, manufacturing engineering, and industrial applications. This book offers a snapshot of the state-of-the-art, highlighting tremendous advances in engineering technologies and physical sciences and their applications, and will serve as an excellent reference for researchers and graduate students working in many different disciplines of physical sciences and engineering.
Assessment and Comparison of Machining Performance -- Heat Transfer Performance for an Obliquely Impinging Slot Jet on a Convex Surface -- Combustion of Coal in Fluidized Bed -- An Experimental Study of Catalysts and Carrier Gas Diffusion -- A Comparison of Loading on a Single or Double Temporomandibular Joint -- Catalytic Membrane Reactor -- Characterization of an Alumina Membrane -- A Motorized Yam Pounding Machine Developed -- Lean Six Sigma Project for Productivity Enhancement -- A Method for Mechanical Design of Am Fabricated Viscoelastic Parts -- Lean Manufacturing Implementation -- Using OWAS in Automotive Subsidiary Sector -- Manufacturing Flexibility as a Strategy -- ORE Processing By PGM Concentration Process and Assessment of Co2 Equivalent Emissions -- Optimal Policies of Condition-Based Maintenance -- Identifying Maintenance Actions -- A Mathematical Model of Integrated Production-Inventory-Distribution System -- Novel Study of Catalysts and Membrane. Maintenance Practice in a Sand Casting Foundry -- A Hybrid Knowledge-Based Lean Six Sigma Maintenance System -- Strategic Leadership Practices for Sustainable Competitive Advantage -- Reinventing the Energy Bill in Smart Cities with NOSQL Technologies -- Using Hurst Exponent and Machine Learning To Build a Predictive Model -- A New Secure Framework in MCC Using Homomorphic Signature -- Security Issues in Content Modification Processes -- Capacity and Range Analysis of a Proposed 5g Wireless Network Solution -- Indoor Localisation Using Multiple Fingerprint Maps -- Extended Performance Research on Wi-Fi IEEE 802.11 A, B, G Laboratory Open Point-To-Multipoint and Point-Topoint Links -- From 3gpp LTE to 5g: An Evolution -- Wireless Body Area Network for Cycling Posture Monitoring -- Reducing Power Consumption of Wireless Sensor Networks -- Microstrip Patch Antenna. .
Keywords: Industrial engineering; Production engineering; Software engineering; Computer vision; Artificial intelligence; Industrial and Production Engineering; Software Engineering; Computer Vision; Artificial Intelligence